Architecture as a means of labour : architecture contributing to contextual events through its consumption a clothing production facility in the City of Pretoria - Van Rensburg, Rudolf Johannes (University of Pretoria, 2013)
Dissertation (MArch(Prof))--University of Pretoria, 2010.